Land forgery, black money rotation with genuine authentication using big data - M. Kiruthiga Devi, Mrs.; N. Ramya, Mrs.; K, Priyanka.; P, Varsha. (International Journal of Engineering and Technology, 2018)
Land forgery is predominant in India, the project aims to eliminate forgery activities while selling and buying the land with the guideline value. The money transaction made during the purchase of property majorly contributes to the black money problem in our country. To overcome this black money rotation and land forgery, both the Buyer and Seller has to register the land with their Aadhaar card to verify the genuineness of them. While verifying, if the system identifies any criminal cases filed against the buyer or seller or the land acquired by the seller is not authorized, it blocks the transaction. The process involves of document unique verification, legal activity verification and black money tracking, all the data are maintained in Hbase database and then integrated and stored in HDFS file storage. Map Reduce programming model is used to retrieve required information from big amount of data at a faster rate. If there are no such issues on the buyer and the seller. The overall transaction amount between the buyer and seller is finally referred to the Income Tax Department. If any illegal activity is detected in the transaction, the alert is sent to the Income Tax department and police officials so that the registration is blocked and black money rotation could be avoided.Â Â